Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.

On the sensitivity of alginate rheology to composition - Suresh, Karthika; Haering, Marleen; Kumaraswamy, Guruswamy; Diaz Diaz, David (Soft Matter, 2019)
The linear response of alginate-phenyl boronic acid (Alg-PBA) esters shows a universal, composition-independent viscoelastic fluid-like behaviour. Reversible association of alginates governs their rheology at all compositions (viz. at all alginate concentrations and solution pH). However, their high strain behaviour is very sensitive to composition. Tuning composition affords liquids that neck to form filaments capable of being drawn to large elongations without failure. We interpret our data by invoking strain-dependent association and dissociation rates for the alginates. High association rates at high strain result in materials with viscoelastic liquid like behaviour.